Workplace toxicity is not just a mental health issue women of color are getting physically sick from work : how can managers disrupt this "tox-sick" pattern? - Purushothaman, Deepa; Rein, Valerie (MIT Sloan Management Review, 2023)
Workplace toxicity leads to a host of negative mental and physical health outcomes, particularly for women of color. Leaders can better support these employees and build a more equitable culture with the guidance offered here, starting with sharing more feedback, shifting organizational processes, and valuing contributions to diversity, equity, and inclusion efforts.
Reprint 64315. - Includes bibliographical references
Keywords: Diversity in the workplace; Personnel management; Multiculturalisme en milieu de travail; Personnel; Direction